(untitled) - Kingdom, William D. (Washington DC, 2005)
Aggregation is defined as the grouping of several municipalities into a single administrative structure for the provision of a particular service. The main driver for aggregation is providing services to a larger customer base more efficiently and at a lower cost. Although aggregation is relatively easy to construct, aggregation has a relatively high risk of failure because it is perceived as too complex, political will is lacking, or the potential benefits are not clearly understood. This study, financed by the Government of the Netherlands through the Bank-Netherlands Partnership Program (BNPP), analyzes the main drivers and constraints to water supply and sanitation (WSS) service aggregation. Aggregation reforms are usually considered when WSS services are too small to be efficient or when decentralization of WSS services to the lowest level of government is not possible. Larger systems can deliver services at a lower unit cost because overhead costs are shared across a wider customer base. Other advantages are that aggregation can take place without the transfer of asset ownership, and that aggregation enhances professional capacity in service providers. However, aggregation can fail if there is no adequate process in place to implement it. Political will and due process are therefore necessary to assist municipalities in carrying out the aggregation process, especially in the case of small towns that lack the required capacity.
Keywords: Water supply,Cung cấp nước